1991
DOI: 10.1021/je00003a004
|View full text |Cite
|
Sign up to set email alerts
|

Shear viscosities of binary liquid mixtures: 2-pyrrolidinone with 1-alkanols

Abstract: Excess viscosities, excess volumes, and free energies of activation for viscous flow of the binary mixtures 2-pyrrolldone + methanol, + ethanol, + 1-propanol, + 1-butanol, and + 1-pentanol were calculated at five different temperatures from density and viscosity measurements. The results obtained suggest that the breaking of the self-associations existing In the pure liquids Is partly balanced by the heteroassociations formed among the molecules of the binary mixtures. These heteroassociations decrease with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(37 citation statements)
references
References 9 publications
4
32
0
1
Order By: Relevance
“…It can be seen that the majority of deviations are lower than ±0.1%, the average absolute deviation (AAD) is about 0.06% (see also Table 3). Most of the data by Zúñiga-Moreno and Galicia-Luna [53] show systematic negative deviations, although the deviations are very close [49]; ( ), [56]; ( ), [71]; (×), [58]; (⊗), [64]; ( ), [74]; (♦), [47]; (+), [65]; ( ), [73]; ( ), [61]; ( ), [70]; ( ), [62]; ( ), [33]; ( ), [72]; (♂), [76]; (♀), [32]; ( ), [75]; ( ), [35]; ( ), [36]; ( ), [21]; (--), calculated with correlation by Khasanshin [92]; (----), calculated with correlation by Marczak et al [47].…”
Section: Comparison With Previous Publicationsmentioning
confidence: 99%
“…It can be seen that the majority of deviations are lower than ±0.1%, the average absolute deviation (AAD) is about 0.06% (see also Table 3). Most of the data by Zúñiga-Moreno and Galicia-Luna [53] show systematic negative deviations, although the deviations are very close [49]; ( ), [56]; ( ), [71]; (×), [58]; (⊗), [64]; ( ), [74]; (♦), [47]; (+), [65]; ( ), [73]; ( ), [61]; ( ), [70]; ( ), [62]; ( ), [33]; ( ), [72]; (♂), [76]; (♀), [32]; ( ), [75]; ( ), [35]; ( ), [36]; ( ), [21]; (--), calculated with correlation by Khasanshin [92]; (----), calculated with correlation by Marczak et al [47].…”
Section: Comparison With Previous Publicationsmentioning
confidence: 99%
“…[15]. Relative deviations of experimental data from literature values at atmospheric pressure [14,[31][32][33][34][35][36][37] and density values calculated with Eq. (1) for 1-pentanol and 2-pentanol are shown in Figs.…”
Section: Is Expressed Bymentioning
confidence: 99%
“…, Sülzner et al [16]. (1) for 1-pentanol at atmospheric pressure; •, Diaz-Peña and Tardajos [31]; , Ortega and Paz-Andrade [32]; , Riggio et al [33]; ♦, Ortega [34]; , Garcia et al [35]; ✩, Garg et al [14]; ×, Indraswati et al [36]; +, Rodriguez et al [37]. …”
Section: Is Expressed Bymentioning
confidence: 99%
“…Further, the excess viscosities of these systems, regardless of their sign, can be generalized by saying that the magnitude of the values, |ŋ Gracia et al 1991 [35] observed that for two pyrolidone + 1-alkanols, excess free energies were found to be positive in case of methanol and negative with higher alcohols. The negative value of ∆G #E for DMF + butanol and DMF + 1-pentanol show agreement with above [35] observation. The sign of, ∆G #E for a system is regarded to be more reliable criterion as to tell about the strength of interaction.…”
Section: Resultsmentioning
confidence: 99%